2013
DOI: 10.1016/j.bpj.2013.04.013
|View full text |Cite
|
Sign up to set email alerts
|

An NMDA Receptor Gating Mechanism Developed from MD Simulations Reveals Molecular Details Underlying Subunit-Specific Contributions

Abstract: N-methyl-D-aspartate (NMDA) receptors are obligate heterotetrameric ligand-gated ion channels that play critical roles in learning and memory. Here, using targeted molecular dynamics simulations, we developed an atomistic model for the gating of the GluN1/GluN2A NMDA receptor. Upon agonist binding, lobe closure of the ligand-binding domain produced outward pulling of the M3-D2 linkers, leading to outward movements of the C-termini of the pore-lining M3 helices and opening of the channel. The GluN2A subunits, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 53 publications
2
65
0
Order By: Relevance
“…All simulations were performed using NAMD version 2.9 (28) with CHARMM27 protein force field and CHARMM36 lipid force field (29). The simulation parameters were the same as those for the previous simulations (30,31).…”
Section: Homology Modeling and Molecular Dynamics Simulation-mentioning
confidence: 99%
“…All simulations were performed using NAMD version 2.9 (28) with CHARMM27 protein force field and CHARMM36 lipid force field (29). The simulation parameters were the same as those for the previous simulations (30,31).…”
Section: Homology Modeling and Molecular Dynamics Simulation-mentioning
confidence: 99%
“…This increased instability likely plays a key role in the functionality of the NMDAR (24)(25)(26)(27)(28)(29). Simulations of the NMDAR LBD suggest that the energy landscape of the protein is broad, even when bound to the primary agonist, indicating that there are many conformations that are weakly stable (19,38). In addition to the conformational changes experienced during normal receptor function, the protein can also unfold due to loss of stability of the folded state (18,39,40).…”
Section: Introductionmentioning
confidence: 95%
“…The NMDAR is unique among the glutamate receptors in that it forms hetero-tetrameric complexes using two glycine-binding GluN1 subunits, and two other subunits, either the glutamate-binding subunit GluN2 or the glycine-binding GluN3 subunit (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Each subunit comprises four main domains-the extracellular N-terminal domain, the ligand-binding domain (LBD), the intracellular C-terminal domain, and the transmembrane domain (14)(15)(16)(17)(18)(19). The LBD cleft, comprised of two lobes connected by a hinge, is responsible for inducing large conformational changes that control the opening and closing of the cation channel, allowing for the regulation of ion concentration into the cell (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on the structural snapshots provided by the crystal structures, we carried out molecular-dynamics simulations in which the LBD clefts were closed to induce channel opening (30,31). These simulations suggested that AMPA and NMDA receptors have similar gating mechanisms, with the M3-D2 linkers playing a crucial role in transmitting the action of LBD cleft closure into the opening of the channel pore.…”
Section: Introductionmentioning
confidence: 99%